Community pharmacy and the extended community pharmacist practice roles: The UAE - Mirai Mourad Sadek; Asim Ahmed Elnour; Naama M.S. Al Kalbani; Akshaya Srikanth Bhagavathula; Mohamed A. Baraka; Alaa Mohammed Abdul Aziz; Abdulla Shehab (Elsevier, 2016)
Background: The pharmaceutical care and 'extended' roles are still not practiced optimally by community pharmacists. Several studies have discussed the practice of community pharmacy in the UAE and have shown that most community pharmacists only counsel patients. However, UAE, has taken initiatives to allow and prepare community pharmacists to practice 'extended' roles. Aim of the review: The aim was to review the current roles of community pharmacists in Abu Dhabi Emirate, United Arab Emirates (UAE). Objective: The objective was to encourage community pharmacists toward extending their practice roles. Methods: In 2010, Health Authority Abu Dhabi (HAAD) surveyed community pharmacists, using an online questionnaire, on their preferences toward extending their counseling roles and their opinion of the greatest challenge facing the extension of their counseling roles. Results: Following this survey, several programs have been developed to prepare community pharmacists to undertake these extended counseling roles. In addition to that, HAAD redefined the scope of pharmacist roles to include some extended/enhanced roles. Abu Dhabi Health Services (SEHA) mission is to ensure reliable excellence in healthcare. It has put clear plans to achieve this; these include increasing focus on public health matters, developing and monitoring evidence-based clinical policies, training health professionals to comply with international standards to deliver world-class quality care, among others. Prior to making further plans to extend community pharmacists' roles, and to ensure the success of these plans, it is imperative to establish the views of community pharmacists in Abu Dhabi on practicing extended roles and to gain understanding and information on what pharmacists see as preferred change strategies or facilitators to change. Conclusions: In an attempt to adapt to the changes occurring and to the growing needs of patients and to maximize the utilization of community pharmacists' unique structured strategies are needed to be introduced to the community pharmacy profession.